Exploitation of Indonesian Migrant Workers on Foreign Ship - Laode Muhammad Fathun; Briando Tanri (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2022)
This paper will explain the strategies that must be carried out by the Indonesian government to minimize transnational crime. Transnational crimes against Indonesian migrant workers working on foreign ships have so far not received special attention. The increase in cases every year, especially 2019-2020 shows that this transnational crime must be a priority for the Indonesian government. Why is this important, it is part of Indonesia's foreign policy and diplomacy to protect the human rights of its citizens. This protection is a form of state commitment to provide a sense of security to humans, especially Indonesian citizens. This paper uses a qualitative method in the form of a case study with secondary data analysis techniques and a thorough literature review. The results obtained are that the strategies that must be carried out by the government are 1) tightening the recruitment channels for migrant workers 2) national and international law enforcement, 3) bilateral and multilateral diplomacy 4) the use of digital applications, and 5) collaboration with NGOs such as the ILO. This paper can become a reference for the government's strategy to formulate a pentahelic policy in solving crimes against Indonesian migrant workers abroad.